2021
DOI: 10.7554/elife.69498
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of N-terminal domains of syntaxin-1 in vesicle fusion from central murine synapses

Abstract: Syntaxin-1 (STX1) and Munc18-1 are two requisite components of synaptic vesicular release machinery, so much so synaptic transmission cannot proceed in their absence. They form a tight complex through two major binding modes: through STX1's N-peptide and through STX's closed conformation driven by its Habc- domain. However, physiological roles of these two reportedly different binding modes in synapses are still controversial. Here we characterized the roles of STX1's N-peptide, Habc-domain, and open conformat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
(188 reference statements)
2
13
0
Order By: Relevance
“…To test whether loss of palmitoylation by STX1A K260E alone and loss of cysteine residues and their palmitoylation would affect the Ca 2+ -channel activity, we monitored Ca 2+ -influx in the presynapse in the neurons additionally transduced with the Ca 2+ -sensor SynGCampf-6 by stimulating them with different numbers of APs ( Figure 5A-C ). As we have previously reported ( Vardar et al, 2021 ), loss of STX1 reduced the global Ca 2+ -influx ( Figure 5A and B ). On the other hand, neither STX1A CVCV nor STX1A K260E showed significantly different SynGCampf-6 signal where the former trended towards an increase for 1AP and the latter trended towards a decrease for 2, 5, 10, and 20 APs ( Figure 5A and C ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To test whether loss of palmitoylation by STX1A K260E alone and loss of cysteine residues and their palmitoylation would affect the Ca 2+ -channel activity, we monitored Ca 2+ -influx in the presynapse in the neurons additionally transduced with the Ca 2+ -sensor SynGCampf-6 by stimulating them with different numbers of APs ( Figure 5A-C ). As we have previously reported ( Vardar et al, 2021 ), loss of STX1 reduced the global Ca 2+ -influx ( Figure 5A and B ). On the other hand, neither STX1A CVCV nor STX1A K260E showed significantly different SynGCampf-6 signal where the former trended towards an increase for 1AP and the latter trended towards a decrease for 2, 5, 10, and 20 APs ( Figure 5A and C ).…”
Section: Resultssupporting
confidence: 89%
“…We inserted three AAs, glycine-serine-glycine (GSG), into the JMD of STX1A either at the junction of its SNARE domain and JMD (STX1A GSG259 ) or of its JMD and TMD (STX1A GSG265 ) ( Figure 1A ), similar to the previous studies ( Hu et al, 2021 ; Kesavan et al, 2007 ; McNew et al, 1999 ; Mostafavi et al, 2017 ; Zhou et al, 2013 ). Using our lentiviral expression system in STX1-null neurons ( Vardar et al, 2016 ; Vardar et al, 2021 ) and electrophysiological assessment, we surprisingly found that the insertion of one extra helical turn into the JMD of STX1A led to position-specific physiological phenotypes ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The functions of the chimeric proteins were determined by locomotion assays ( Figures 1 A and 1B) and sensitivity to the acetylcholine—esterase inhibitor aldicarb ( Figure 1 C)—resistance to the drug implies a reduced level of acetylcholine release ( Mahoney et al., 2006 ). The N-peptide swap only exhibited subtle changes to locomotion, consistent with some previous experiments ( Meijer et al., 2012 ; Park et al., 2016 ; Vardar et al., 2021 ), but not all ( Hu et al., 2007 ; Shen et al., 2007 , 2010 ; Zhou et al., 2013 ). The replacement of the linker domain resulted in significant defects in locomotion and aldicarb sensitivity.…”
Section: Resultssupporting
confidence: 90%
“…In agreement, the deletion of the Habc domain from Sso1 increases SNARE complex assembly over 2000-fold ( Nicholson et al., 1998 ). However, the deletion of the yeast Vam3 Habc domain ( Lürick et al., 2015 ), the mouse syntaxin Habc domain ( Vardar et al., 2021 ; Zhou et al., 2013 ), and the worm syntaxin Habc domain ( Rathore et al., 2010 ) all decreased fusion. The decrease in fusion could be attributed to poor trafficking ( Fan et al., 2007 ; Medine et al., 2007 ; Yang et al., 2006 ) or poor expression ( Vardar et al., 2021 ; Zhou et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation